Channel Morphological Characteristics and Morphodynamic Processes of Large Braided Rivers in Response to Climate‐Driven Water and Sediment Flux Change in the Qinghai‐Tibet Plateau - Yucong He; Zhiwei Li; Junqiang Xia; Shanshan Deng; Yinjun Zhou (Water Resources Research)
Abstract With rising air temperature and precipitation, water and sediment fluxes in the Source Region of the Yangtze River (SRYR) have increased since 2000s. Nonetheless, the response of braided river morphology to climate‐driven water and sediment flux change is still unknown. Water bodies of 9 large braided rivers from 1990 to 2020 were extracted based on Google Earth Engine platform, and impacts of climate change on morphological indices and morphodynamic processes were quantified. A new segmentation method is presented to more precisely extract braided river water body when the branch width is less than an image pixel size. The warming and wetting trend led to vegetation cover increase. With the increase of water flux, the water area of each braided reach has increased in both flood and non‐flood season. The 3–5 years mean annual erosion and accretion intensity (newly proposed in this study) of the channel shows three different trends of increasing, weakening, and unchanged over time. These three trends can be classified into three patterns in response to climate‐change driven water and sediment flux change in the SRYR as follows: sediment increase constrained pattern (weakening or unchanged), sediment increase dominated pattern (increasing), and water increase dominated pattern (increasing or unchanged). In summary, the braided rivers in the SRYR showing consistent increasing of water area, general expansion of active channel, and increasing of erosion and accretion intensity for some of the rivers, with the climate‐driven increasing water and sediment flux.